Clinical and morphological phenotypes in intrathoracic sarcoidosis - I. A. Palchikova; O. A. Denisova; G. M. Chernyavskaya; I. L. Purlik; T. P. Kalacheva; A. O. Naumov; M. M. Soloviev (Бюллетень сибирской медицины)
Aim. To study clinical and morphological phenotypes in different variants of the course of intrathoracic sarcoidosis and isolate new phenotypes.Materials and methods. The study included 121 patients with intrathoracic sarcoidosis aged 21–66 years (50.4% were men, 49.6% were women, the average age at the time of the disease onset was 38 years) over the period 2007– 2019. During the examination, patients’ complaints were studied thoroughly, and the diagnosis was histologically verified in all cases. During an extended histological examination, the quantitative and qualitative composition of biopsy specimens was investigated. The number of granulomas in the field of vision and the content of giant cells, macrophages, lymphocytes, neutrophils, and eosinophils in them were studied. Qualitative parameters were assessed for the presence of hyalinosis, Schaumann bodies, necrosis, stamping, calcification, fibrosis, and vasculitis. All patients were retrospectively divided into two clinical groups depending on the outcomes of the disease: group 1 included patients with a favorable course of sarcoidosis, proceeding without relapses and signs of progression; group 2 encompassed patients with an unfavorable course of the disease with relapses and progression, requiring long-term administration of systemic glucocorticoids.Results. The analysis showed that among all general clinical manifestations, only the presence of dyspnea, skin manifestations, and weight loss occurred significantly more often in the patients with an unfavorable course of intrathoracic sarcoidosis (р = 0.04; 0.02; and 0.01, respectively). Among morphological parameters, a large number of macrophages was significantly more frequent in the biopsy specimens in this group of patients (р < 0.01).